ANALISIS YURIDIS PEMINDAHAN TANAH WAKAF DITINJAU DARI HUKUM ISLAM DAN UNDANG-UNDANG NOMOR 41 TAHUN 2004 TENTANG WAKAF (STUDI PUTUSAN PTUN NO: 98/G/2011/PTUN.JKT) - ELVIRA LIESHANTY FEBRYZA (PREMISE LAW JURNAL, 2016)
In the opinion of Imam Syafi’i, wakaf property cannot be tranferred bu any reasons. Article 40 of law No.41/2004 on Wakaf states that wakaf property cannot be used a collateral, confiscated, given sold, bequeathed, changed, and transferred in the form of transfer of title. However, there is anexception in law No.41/2004 on Wakaf, for the sake of public interest according to RUTR (General Layout Plan), based on the regulations in forceand is not contrary to sharia. The process of transferring the wakaf land of Raudhatul Islam mosque is administratively defective and so are the Islamic provisions and law on wakaf. The verdict No. 98/G/2011/PTUN.JKT is contrary to legal provisions, the theory of justice, legal certainty, and social welfare. Keywords: Wakaf land transfer, Islamic Law, Law no.41/2004 on Wakaf